2013
DOI: 10.1016/j.oceaneng.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of a flexible yacht sail plan

Abstract: A numerical investigation of the dynamic Fluid Structure Interaction (FSI) of a yacht sail plan submitted to harmonic pitching is presented to address both issues of aerodynamic unsteadiness and structural deformation.The FSI model -Vortex Lattice Method fluid model and Finite Element structure model -has been validated with full-scale measurements. It is shown that the dynamic behaviour of a sail plan subject to yacht motion clearly deviates from the quasi-steady theory. The aerodynamic forces presented as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…A comparison between a rigid structure and a realistic soft structure showed that the hysteresis still exists for a rigid structure 6 but it is lower than when the structure deformation is taken into account. However, in this first work (Augier et al [2013]), the question whether this hysteresis could be represented by a simple phase shift between both oscillating signals was not clearly elucidated. Moreover, the energy exchange associated to the hysteresis phenomenon was not determined.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A comparison between a rigid structure and a realistic soft structure showed that the hysteresis still exists for a rigid structure 6 but it is lower than when the structure deformation is taken into account. However, in this first work (Augier et al [2013]), the question whether this hysteresis could be represented by a simple phase shift between both oscillating signals was not clearly elucidated. Moreover, the energy exchange associated to the hysteresis phenomenon was not determined.…”
Section: Introductionmentioning
confidence: 89%
“…In a previous work (Augier et al [2013]), the aero-elastic behaviour of the sail plan subjected to a simple harmonic pitching was numerically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been subject to a large number of experimental studies to measure both the aerodynamic loads on the boat frame using a balance (Flay, 1996;Viola and Flay, 2009;Fossati and Muggiasca, 2011;Campbell, 2014) and the pressure and 3D shape deformation of the structure (Graf and Müller, 2009;Viola and Flay, 2011;Viola et al, 2013). Recent studies have highlighted the non-trivial effect of dynamic oscillation on the aerodynamic forces (Gerhardt et al, 2011;Fossati and Muggiasca, 2011;Augier et al, 2013Augier et al, , 2014a. Nevertheless, wind tunnel testing violates some rules of similitudes as Reynolds number, the ratio of fabric weight or membrane stress to wind pressure (Flay, 1996) and cannot reproduce properly all the physical phenomena present at full-scale.…”
Section: Mavmentioning
confidence: 99%
“…Another configuration is to measure the forces separately in the rigging line as developed by Augier et al (2012) in upwind condition and Deparday et al (2014) for downwind condition with spinnakers. External load sensors can be coupled to other sensors in order to measure the sail shapes with camera recognition (Augier et al, 2012(Augier et al, , 2013, the forces and the directions on the three corners of spinnakers , pressures on sails for upwind and downwind sails (Viola and Flay, 2010;Le Pelley et al, 2012;Lozej et al, 2012;Motta et al, 2014;Deparday et al, 2014).…”
Section: System Apparatusmentioning
confidence: 99%
“…The above outlined challenges are akin to those involved in other FSI applications [19,20], such as the spacecraft aerodynamics [69], FSI modeling of spacecraft parachutes [68, 71, 73-76, 80, 81, 84], sails [4,5,91], cardiovascular fluid mechanics and FSI [10,13,14,30,49,60,61,64,70,72,78,79,83], pulsatile ventricular assist devices [48,50,51], and bioprosthetic heart valves [32,33,38], and are addressed in the present paper in order to carry out the tandem hydrofoil FSI simulations. A moving-mesh FSI methodology is employed in the present work.…”
Section: Introductionmentioning
confidence: 99%